Quercetin decreases cardiac hypertrophic mediators and maladaptive coronary arterial remodeling in renovascular hypertensive rats without improving cardiac function - Eduardo Vieira da Rocha; Francisco Falchetti; Laena Pernomian; Marcela M. Blascke de Mello; Juliana M. Parente; Renato C. Nogueira; Beatriz Q. Gomes; Giuliana Bertozi; Jessica M. Sanches-Lopes; José Eduardo Tanus-Santos; Michele M. Castro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Internal tides in the central Mediterranean Sea: observational evidence and numerical studies - P. Oddo; P. M. Poulain; S. Falchetti; A. Storto; G. Zappa (Ocean Dynamics, 2023)
Internal tides are studied in the central Mediterranean Sea using observational data and numerical experiments. Both numerical results and observations indicate that the baroclinic variability in this area is dominated by the K1 diurnal tide. In agreement with previous studies, the diurnal internal tides have the characteristics of Kelvin-like bottom trapped waves. They are mainly generated by the interaction of the induced barotropic tidal flow with the steep bathymetric gradient connecting the Ionian Sea with the shallow Sicily Channel. The bathymetric gradient appears to be the major forcing shaping the propagation paths of the internal tides. The most energetic internal tides follow the steep bathymetric gradient, propagating southward and tending to dissipate rapidly. Other waves cross the continental shelf south of Malta and then split with one branch moving toward the southern coast of Sicily and the other moving toward the west. Internal tides propagate with a variable phase velocity of about 1 ms −1 and a wavelength of the order of 100 km. During their journey, the internal waves appear to be subject to local processes that can modify their characteristics. The induced vertical shear strongly dominates the vertical turbulence and generates vertical mixing that alters the properties of the water masses traversing the area. Barotropic and internal tides remove heat from the ocean surface, increasing atmospheric heating, and redistributing energy through increased lateral heat fluxes. Lateral heat fluxes are significantly greater in the presence of internal tides due to the simultaneous increase in volume fluxes and water temperatures.

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

Correlation between serological immune response analyzed by a new ELISA for HPV-16/18 E7 oncoprotein and clinical characteristics of cervical cancer patients - A. Ravaggi; C. Romani; B. Pasinetti; R. A. Tassi; E. Bignotti; E. Bandiera; F. E. Odicino; M. Ragnoli; C. Donzelli; M. Falchetti; S. Calza; A. D. Santin; et al. (Archives of Virology, 2006)